Patient perceptions of inhaled asthma medications: a qualitative study in Northern Sri Lanka - Guruparan, Y.; Thiyahiny, S.N.; Kumar, R.; Gowry, S.; Shalini, S.R. (BMJ Open, 2026)
Objectives This study explores perceptions of inhaled medications among patients with asthma at an outpatient tertiary care setting in Northern Sri Lanka. Design A descriptive qualitative research design was used to gather data through focus group discussions (FGDs) that were transcribed, translated, manually coded and thematically analysed using Braun and Clarke’s six-step approach. Setting The study was conducted at an outpatient medical clinic at a tertiary care centre in Northern Sri Lanka. Participants Six FGDs were carried out among adult patients with asthma who had been on inhaled medications for at least 3 months. Participants were selected by maximum variation sampling, with each FGD consisting of 6–10 participants. Results 51 participants between the ages of 20 and 71 years were recruited; 36 (70.6%) were female, and about a fourth had primary education or less. Seven subthemes were drawn out and organised into three overarching themes: (1) inhaler hesitancy; (2) fear-driven adherence and (3) conviction at last. Most participants were initially reluctant to use inhalers, primarily due to concerns about dependency and side effects, often influenced by opinions of family members. They delayed use until they experienced severe symptoms, with some describing nebulisation, hospitalisation and fear of death as turning points. Symptom alleviation and improved quality of life led to better adherence. Conclusions Delays in inhaler use could lead to poor asthma control and outcomes. As many patients reported using their inhalers more consistently after an exacerbation or hospitalisation, asthma education programmes, involving both patients and family members, could address context-specific beliefs and misconceptions to promote early and sustained adherence to inhaled medications.